Pemetaan Buku Cerita Anak di Indonesia 1975-1985: Indonesia - Sihombing, Riama Maslan; Zundaro, Naidi Atika; Wiratmo, Triyadi Guntur; Rachmadian, Anneke Defa (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2024)
This study examines the development of children's storybooks in Indonesia during the period of 1975-1985, known as the golden age of children's literature. Using a qualitative approach and Content Analysis method, this study maps 131 children's book titles in terms of publishing aspects and visual characteristics. The results show that the development of children's storybooks in this era was heavily influenced by the Presidential Instruction No. 10 of 1973 and the removal of paper subsidies. Mapping of publishing aspects reveals the dominance of male authors and illustrators, as well as the significant role of publishers such as Pustaka Jaya, Gramedia, and Balai Pustaka. The majority of books have 50-70 pages with text dominating. Analysis of visual characteristics shows a preference for simplified style, outline and shading techniques, and the dominance of black and white colors. Visual representation is dominated by human characters in everyday life settings, with portrait visual structure and symmetrical composition. The themes raised tend to be monotonous, often reflecting government propaganda. This research highlights the importance of documentation and recognition of the contributions of writers and illustrators of that era, and provides valuable insights into the dynamics of the children's publishing industry in Indonesia during the New Order era. keyword: children's storybooks, illustration, New Order, propaganda, content analysis